Physicochemical, functional and emulsifying properties of plant protein powder from industrial sesame processing waste as affected by spray and freeze drying - Özdemir, Elif Ezgi; Görgüç, Ahmet; Gençdağ, Esra; Yılmaz, Fatih Mehmet (Food science & technology, 2022)
This study aimed to produce protein hydrolysates from sesame bran using ultrasound-assisted enzymatic extraction followed by spray-drying (SD) and freeze-drying (FD) techniques. Spray drying parameters highly influenced powder yield (22.8–70.5%), protein yield (23.0–70.4%), drying time (41–149 min) and aw value (0.196–0.288). Therefore, the impacts of SD and FD were assessed after an optimization study. Drying techniques significantly affected amino acid, mineral and lignan compositions as well as proximate powder properties. FD revealed significantly improved wettability (2.3 s) and dispersibility (98.6%) values with higher foaming capacity (35%). Protein powders produced by FD had considerably lower bulk and tapped densities which are important parameters for processing and transportation. On the other hand, SD provided higher water holding capacity (0.94 g H2O/g protein) and better color properties (L*: 71.4). The newly developed protein powder as a functional ingredient could offer sustainable options to food industry and may open up new opportunities to be used in various food formulations. [Display omitted] •A novel plant protein powder was successfully produced from the food waste sesame bran.•Spray dryer conditions largely affected powder/protein yields, process time and aw.•Drying techniques had variable significant effects on the techno-functional properties.•Sesame bran protein powder bears convenient emulsion, solubility and flow properties.•Sesame bran can be a sustainable protein source with its balanced amino acid composition.